DELMAN DAN MEDIA SOSIAL DALAM PENGEMBANGAN PARIWISATA DI JAKARTA - Imam Budi Hartono; Dyah N Ratnasari; Ridwan Akbar; Suryadi Jaya Purnama (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2022)
Delman is a traditional Indonesian vehicle that is commonly seen. Wagons are marginalized in Jakarta due to the presence of public transportation. Delman is now widely used by locals for recreational activities in the afternoon or during holidays while taking in the scenery. The purpose of this paper, in the context of the preservation and development of wagons as tourism attractions, can be accomplished by training wagon coaches as tourism agents while also making wagons iconic in tourism attractions. In order to promote instagrammable spots, the methods used to achieve goals through social media are crucial. The method used was a descriptive qualitative study with a library component. It can be concluded that: (1) Wagon conservation can be accomplished by making the wagon a strong attraction in promoting tourism in Jakarta; (2) Social media is the best way to attract tourists to come by wagon to interesting spots and tourist attractions in Jakarta; and (3) The DKI Jakarta Government's policy is to actively engage in the continued existence of the wagons by enhancing the capacity of wagon coachmen as tourism agents. Keywords: Delman, Social Media, Tourist Attraction, Jakarta.